A eficácia das decisões de controle concentrado de constitucionalidade nos sistemas italiano e espanhol - FREITAS, Juliana Rodrigues (Universidade Federal do Pará, 2017)
The Italian´s and Spanish´s systems of concentrated control of constitutionality have features that distance them from the pure kelsen´s model and, at the same time, allow us to identify them with the North American´s model of constitutionality control. The assignment of binding effect, in horizontal and vertical planes, to the constitutional decisions, even if it is not an element used to identify, so immediately, the constitutional jurisdiction of the European countries, is, undoubtedly, one of its characteristic elements, and gives rise, in this context, to the figure of the previous binding. So for these precedents may be adopted in regard to the principle of equality in law enforcement, it is essential that requirements are defined in a reasonable and objective way, due to the Constitutional Courts gives effect binding to its decisions.